2021
DOI: 10.1161/jaha.121.022560
|View full text |Cite
|
Sign up to set email alerts
|

Causal Effect of Obstructive Sleep Apnea on Atrial Fibrillation: A Mendelian Randomization Study

Abstract: Background Obstructive sleep apnea (OSA) has shown to be associated with an increased risk of atrial fibrillation in observational studies. Whether this association reflect causal effect is still unclear. The aim of this study was to evaluate the causal effect of OSA on atrial fibrillation. Methods and Results We used a 2‐sample Mendelian randomization (MR) method to evaluate the causal effect of OSA on atrial fibrillation. Summary data o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 32 publications
0
28
0
1
Order By: Relevance
“…An association between OSA and increased risk of AF in community and sleep clinic cohorts has been reported in observational studies [ 4 , 5 , 6 ] and observational meta-analysis reported reduced AF recurrence with CPAP therapy [ 7 ]. Similarly, a recent MR study reported a Mendelian randomisation association between genetically proxied OSA and AF, though only five SNPs were instrumented in this analysis, with two associated with BMI or whole-body, fat-free mass at the genome-wide significance level [ 20 ]. Our study builds on these data by including almost six-fold more SNPs significantly correlated with sleep apnoea traits, in addition to performing multivariable MR to control for the well-characterised, powerful pleiotropic effects of BMI on the relationship between SDB and AF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An association between OSA and increased risk of AF in community and sleep clinic cohorts has been reported in observational studies [ 4 , 5 , 6 ] and observational meta-analysis reported reduced AF recurrence with CPAP therapy [ 7 ]. Similarly, a recent MR study reported a Mendelian randomisation association between genetically proxied OSA and AF, though only five SNPs were instrumented in this analysis, with two associated with BMI or whole-body, fat-free mass at the genome-wide significance level [ 20 ]. Our study builds on these data by including almost six-fold more SNPs significantly correlated with sleep apnoea traits, in addition to performing multivariable MR to control for the well-characterised, powerful pleiotropic effects of BMI on the relationship between SDB and AF.…”
Section: Discussionmentioning
confidence: 99%
“…In this way, MR can potentially overcome limitations associated with classical observational epidemiology, namely confounding and reverse causality [ 19 ], and may permit delineation of complex pathways relating SDB, BMI and AF. A recent univariable MR study reported a causal association between five single-nucleotide polymorphisms (SNPs) associated with OSA and AF [ 20 ]. However, some of the employed OSA instruments were also associated with BMI or whole-body, fat-free mass at the genome-wide significance level, raising the question of whether this relationship was partially mediated via obesity.…”
Section: Introductionmentioning
confidence: 99%
“…With an instrumental variable analysis and a huge sample size, the MR approach can be used to study a cause-and-effect relationship without interferences of bias and confounding that are hard to circumvent in observational design, thus it is more appropriate for our exposure and outcome set. Chen (39) did an MR analysis to investigate the association between OSA and AF. They reported that OSA was related to an increased risk of AF.…”
Section: Discussionmentioning
confidence: 99%
“…One Mendelian randomisation study showed that the genetic propensity for obstructive sleep apnoea also increased AF risk (odds ratio 1.21 (95% confidence interval 1.12 to 1.31)). 66 However, this analysis was based on only five single nucleotide polymorphisms, of which two were also associated with body mass index or fat-free mass at the genome wide significance level, suggesting this link could be mediated by obesity. Indeed, another Mendelian randomisation study including almost sixfold single nucleotide polymorphisms showed that although obstructive sleep apnoea was associated with AF in univariable analysis (odds ratio 2.09 (95% confidence interval 1.10 to 3.98)), this finding became non-significant after adjustment for body mass index (0.68 (0.42 to 1.10)).…”
Section: Obstructive Sleep Apnoeamentioning
confidence: 97%